Comparative advantage, demand for external finance, and financial development - Do, Quy-Toan; Levchenko, Andrei A. (Journal of Financial Economics, 2007)
This paper analyzes the effect of comparative advantage in international trade on a country's level of financial development. Countries with comparative advantage in financially intensive goods experience a higher demand for external finance, and therefore financial development. By contrast, financial development is lower in countries that primarily export goods which do not rely on external finance. We use disaggregated trade data to develop a measure of a country's external finance need of exports, and demonstrate this effect empirically. In order to overcome the simultaneity problem, we develop a novel instrumentation strategy based on the exogenous geographic determinants of trade patterns.